MARKET ORIENTATION OF THE MARKETING STRATEGY OF SMALL BUSINESSES (Spectrum Journal of Innovation, Reforms and Development, 2023)
The article presents the results of a study to determine the characteristics of the market orientation of a small business marketing strategy. Taking into account the significance of the development of small and medium-sized businesses, as well as the proven theoretical connection between market orientation and entrepreneurial activity, features of adapting this concept for small and medium-sized enterprises are presented. According to the results of the study, when implementing market orientation, not only the main problem areas faced by small businesses were identified, but also the advantages and necessary conditions for its development in this area: the level of market orientation of small businesses, knowledge (understanding) of the essence of entrepreneurship and its values , establishing close relationships with consumers and major retailers, and integrating marketing. All this, as a result, provides a common platform for creating a market-oriented situation and improving it will help to better understand the processes necessary to orient an enterprise to the market and consumers.